Transcript of Conversation with David Malpass and Samantha Power on the Way Forward - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by the World Bank Group President David Malpass in conversation with Samantha Power, USAID Administrator on June 21, 2022. They discussed about the impact of overlapping global crises on the poorest and most vulnerable people. The world, as people know, is in a very complicated situation, especially for people in poorer countries and the poor worldwide. It has to do with inflation, with food, with conflict, fragility, issues that we work with every day at the World Bank and USAID does, too. As people know, the World Bank works on an array of development issues and including and especially right now food and fertilizer. We have announced 30 billion dollars of assistance in the food-related areas as part of our response to the current set of crises. And one of the challenges is, in specific country areas, to find the right program. And we work very, very closely with development assistance agencies around the world, including and especially USAID.